2021
DOI: 10.1080/09546634.2020.1866741
|View full text |Cite
|
Sign up to set email alerts
|

Disease burden and treatment history among adults with atopic dermatitis receiving systemic therapy: baseline characteristics of participants on the EUROSTAD prospective observational study

Abstract: Background: Insights into the real-world treatment paradigm and long-term burden of atopic dermatitis (AD) are needed to inform clinical and health policy decisions. Methods: The prospective, observational EUROSTAD study enrolled adults with moderate-to-severe AD starting or switching systemic therapy (51 sites in 10 European countries). We report the baseline characteristics, treatment patterns, and outcomes of these patients using descriptive statistics. Results: A 12-month enrollment period of EUROSTAD was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 51 publications
(51 reference statements)
5
16
0
2
Order By: Relevance
“…In general, the likelihood of having a comorbidity increased with the use of systemic treatments, which might be expected since use of systemic treatments is likely to reflect patients with more severe disease. Similar to our findings, the EUROSTAD prospective observational study recently reported a high level of comorbidities, AD burden, and impact on work and daily activities [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In general, the likelihood of having a comorbidity increased with the use of systemic treatments, which might be expected since use of systemic treatments is likely to reflect patients with more severe disease. Similar to our findings, the EUROSTAD prospective observational study recently reported a high level of comorbidities, AD burden, and impact on work and daily activities [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…With newly emerging therapies and further treatments in development [ 1 , 23 , 24 ], there is a continuous need to better understand the burden of disease and real-world treatment patterns for adults with moderate to severe AD in European countries, particularly the barriers regarding conventional (and on-label) treatments and limitations of their use. Findings from recent analyses of treatment patterns in the UK [ 25 ], Europe [ 26 ], and the USA [ 27 , 28 ] suggest a lack of disease control with established therapies and an unmet need for safe and effective targeted agents for long-term disease control [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the mean (SD) DLQI scores in the present study (13.9 [7.1]) were more similar to those reported in the PsoBest registry (12.4 [3.4]) [ 21 , 22 ]. Consistently, the physician- and patient-reported severity and burden of AD in PROLEAD were also greater than those reported in the TREATgermany AD registry and prospective, observational, European-wide EUROSTAD study, as indicated by mean respective EASI (22.9 vs. 16.1 vs. 16.2, respectively), SCORAD (63.3 vs. 40.96 vs. not reported), Peak Pruritus NRS (7.4 vs. not reported vs. 5.5), DLQI (13.9 vs. 11.8 vs. 11.8), and POEM (20.4 vs. 16.8 vs. 17.0) scores [ 23 , 24 ]. Mean IGA scores in PROLEAD (3.3) were comparable to those in EUROSTAD (3.1) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, the physician- and patient-reported severity and burden of AD in PROLEAD were also greater than those reported in the TREATgermany AD registry and prospective, observational, European-wide EUROSTAD study, as indicated by mean respective EASI (22.9 vs. 16.1 vs. 16.2, respectively), SCORAD (63.3 vs. 40.96 vs. not reported), Peak Pruritus NRS (7.4 vs. not reported vs. 5.5), DLQI (13.9 vs. 11.8 vs. 11.8), and POEM (20.4 vs. 16.8 vs. 17.0) scores [ 23 , 24 ]. Mean IGA scores in PROLEAD (3.3) were comparable to those in EUROSTAD (3.1) [ 24 ]. The results of the present and previous studies investigating dupilumab demonstrate the potential to improve management of moderate-to-severe AD.…”
Section: Discussionmentioning
confidence: 99%
“…Atopic dermatitis (AD) is a chronic, inflammatory skin disease. 1 Signs and symptoms, including eczematous lesions and intense itch, can be highly debilitating, 2,3 leading to significant impact on sleep, [4][5][6] mental health, 7,8 health-related quality of life (HRQoL), 2,4,[8][9][10] work productivity, 4,10 and social interactions. 2,4 In addition, this burden appears to directly correlate with increasing disease severity.…”
Section: Introductionmentioning
confidence: 99%